Tropical cyclone Wind Pump induced chlorophyll-a enhancement in the South China Sea: A comparison of the open sea and continental shelf - Li, Ying; Tang, Danling (Frontiers in Marine Science, 2022)
The continental shelf and open sea region have different ocean physical and environmental responses to tropical cyclones (TC). The present study firstly compared the grid-based maximum response (GMR) of sea surface chlorophyll a (Chl-a) to TCs Wind Pump between the continental shelf (depths 50-200m) and open sea (depths>200 m) region in the South China Sea (SCS) during 1998-2020, using multiple-satellite data. For all TC events, the average Chl-a increases by 0.13 mg/m3. The comparisons between the pre- and post-TC periods show that Chl-a increases by 0.18 mg/m3 (115%) in the continental shelf and 0.07 mg/m3 (57%) in the open sea region, respectively. In both areas, TC-induced Chl-a enhancement (Chl_en) strongly depends on TC maximum wind speed and translation speed. The strong and fast-moving TCs and weak and slow-moving TCs both induce the maximum Chl_en in the continental shelf region. While in the open sea, the maximum Chl_en was induced by the strong and slow-moving TCs. Overall, our results reveal that the TC wind pump’s effects on Chl-a enhancement are stronger in the continental shelf region than in the open sea.